2022
DOI: 10.1145/3514500
|View full text |Cite
|
Sign up to set email alerts
|

Federated Learning for Electronic Health Records

Abstract: In data-driven medical research, multi-center studies have long been preferred over single-center ones due to a single institute sometimes not having enough data to obtain sufficient statistical power for certain hypothesis testings as well as predictive and subgroup studies. The wide adoption of electronic health records (EHRs) has made multi-institutional collaboration much more feasible. However, concerns over infrastructures, regulations, privacy and data standardization present a challenge to data sharing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…[ [73][74][75][76] Lab data Mortality A model to predict mortality in intensive care units using FL was built.…”
Section: Data Typesmentioning
confidence: 99%
“…[ [73][74][75][76] Lab data Mortality A model to predict mortality in intensive care units using FL was built.…”
Section: Data Typesmentioning
confidence: 99%
“…Te experimental results revealed that Fed-DNN-Debugger signifcantly improved the model performance and efectively fxed the federated model (Table 2). for each user n from 0 to N in parallel do (5) w t+1 n ⟵ ClientDebugger(n, w t ) (6) end for (7)…”
Section: Debugging Federated Modelsmentioning
confidence: 99%
“…To obtain the two parameters, Table 3 shows the experimental results of the model performance with diferent proportions of the selected data in the retraining dataset. From left to right, the table shows the dataset, proportion of selected high-quality samples in the retraining dataset, and (in columns [3][4][5][6][7][8][9][10][11] the number of retraining samples. We can observe that the model achieved the best performance when the ratio was 0.3 and the number of retraining samples was 4000.…”
Section: Debugging Federated Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…EHR is considered one of the prominent sources of healthcare data for FL applications. A detailed survey of existing works on EHR data for FL applications is outlined in [226]. Training an ML/AI algorithm on EHR data from a single hospital might introduce some amount of bias and may not be generalizable.…”
Section: B Statistical Challengesmentioning
confidence: 99%